2012
DOI: 10.1007/s10826-012-9658-1
|View full text |Cite
|
Sign up to set email alerts
|

Factorial and Construct Validity of FACES IV Among Italian Adolescents

Abstract: The aims of this study were to evaluate the reliability, validity and factorial structure of Family Adaptability and Cohesion Evaluation Scale, Version IV (FACES IV), investigate the relevance of sex and age on family functioning and study the relationship between family functioning and adolescents' perception of parent and peer attachment. The sample consisted of 1,416 participants (672 women, 744 men, M-age = 17.38 years; age range = 13-22 years) divided into three age groups: 13-15, 16-18, and 19-22 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
80
3
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 28 publications
13
80
3
9
Order By: Relevance
“…Previous reports on the internal consistency of the FACES enmeshment subscale are inconsistent. While some researchers have reported stronger internal consistencies than yielded in this study, ranging from .75 (Franklin et al 2001) to .77/.78 (Mirnics et al 2010;Olson 2011), to .89 J Child Fam Stud (Rivero et al 2010), other researchers have reported alpha coefficient estimates comparable to the one reported here, ranging from .65 (Marsac and Alderfer 2011) to .67 (Baiocco et al 2013).…”
Section: Resultssupporting
confidence: 46%
“…Previous reports on the internal consistency of the FACES enmeshment subscale are inconsistent. While some researchers have reported stronger internal consistencies than yielded in this study, ranging from .75 (Franklin et al 2001) to .77/.78 (Mirnics et al 2010;Olson 2011), to .89 J Child Fam Stud (Rivero et al 2010), other researchers have reported alpha coefficient estimates comparable to the one reported here, ranging from .65 (Marsac and Alderfer 2011) to .67 (Baiocco et al 2013).…”
Section: Resultssupporting
confidence: 46%
“…A further improvement brought on by the Balanced and Unbalanced ratio score is that it offers a method to assess the curvilinearity of Cohesion and Flexibility dimensions. These scales proved to be valid, reliable, and discriminatory among both problematic and non-problematic families, and the range of reliability in the six scales, in this study, is between .74 and .87 (Baiocco et al, 2013). (Barnes and Olson, 1985); the PACS is a 20-item scale developed to measure communication in families with an adolescent.…”
Section: Measurement Family Adaptability and Cohesion Evaluation Scalmentioning
confidence: 66%
“…The FSS has an alpha reliability of 0.93 and test–retest reliability of 0.85. In this study, internal consistency reliability is 0.91 and we used the normative scores of the Italian version of FACES-IV and family members’ scores were averaged to yield an overall family score 5456…”
Section: Methodsmentioning
confidence: 99%